2015
DOI: 10.1073/pnas.1424440112
|View full text |Cite
|
Sign up to set email alerts
|

Postmitotic regulation of sensory area patterning in the mammalian neocortex by Lhx2

Abstract: Current knowledge suggests that cortical sensory area identity is controlled by transcription factors (TFs) that specify area features in progenitor cells and subsequently their progeny in a one-step process. However, how neurons acquire and maintain these features is unclear. We have used conditional inactivation restricted to postmitotic cortical neurons in mice to investigate the role of the TF LIM homeobox 2 (Lhx2) in this process and report that in conditional mutant cortices area patterning is normal in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 41 publications
(73 reference statements)
4
47
0
Order By: Relevance
“…6A). Finally, when area patterning was examined using Serotonin (5-HT) immunostaining on tangential sections of the flattened cortex, which reveals terminations of thalamocortical axons in cortical layer 4 of the corresponding primary sensory areas (Fujimiya et al, 1986; Zembrzycki et al, 2015a), we found no differences in overall cortical or area sizes and their patterning between wild type and Foxg1-IRES-Cre heterozygous mice (Fig. 6B).…”
Section: Resultsmentioning
confidence: 91%
“…6A). Finally, when area patterning was examined using Serotonin (5-HT) immunostaining on tangential sections of the flattened cortex, which reveals terminations of thalamocortical axons in cortical layer 4 of the corresponding primary sensory areas (Fujimiya et al, 1986; Zembrzycki et al, 2015a), we found no differences in overall cortical or area sizes and their patterning between wild type and Foxg1-IRES-Cre heterozygous mice (Fig. 6B).…”
Section: Resultsmentioning
confidence: 91%
“…A recent study combining serial analysis of gene expression and transcription factor binding site prediction identified 64 novel candidate target genes of NR2E1 involved in neocortical development (Schmouth et al, 2015). These include LHX2, which is involved in "post-mitotic regulation of sensory area patterning in the mammalian neocortex" (Zembrzycki, Perez-Garcia, Wang, Chou, & O'Leary, 2015) and its cofactor SOX9. It is also known that coordination and cooperation between NR2E1 and PAX6 is required for brain patterning during development (Stenman, Yu, Evans, & Campbell, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an obvious question is whether the effects of LHX2 removal are relevant in the ventricular zone progenitors themselves, or in the newly postmitotic neurons they produce. A recent study that used NexCre to delete LHX2 specifically in postmitotic neurons starting from E11 offers clarity on this issue (Zembrzycki et al, 2015). This study elegantly demonstrated that NexCre action is not seen in proliferating progenitors in the ventricular zone but is seen in newly postmitotic cells (Zembrzycki et al, 2015, their Figure S2) and that molecular specification of the different cortical layers is not affected (Zembrzycki et al, 2015, their Fig.…”
Section: Discussionmentioning
confidence: 99%